Clinical findings, diagnostics and outcome in 33 cats with adrenal neoplasia (2002–2013). Issue 2 (February 2016) - Daniel, Gideon; Mahony, Orla M; Markovich, Jessica E; Appleman, Elizabeth; Monaghan, Kelly N; Lawrence, Yuri A; Fiocchi, E Hathaway; Weaver, Kelli; Johnston, Andrea; Barton, Bruce
Objectives: The objective of this retrospective study was to describe the clinical signs and diagnostic findings in cats with histopathologically confirmed adrenal neoplasms, and to assess correlations with survival data. Methods: Study data were acquired by reviewing medical records for all cats diagnosed with adrenal neoplasms at seven referral institutions between 2002 and 2013. Inclusion criteria required a histopathologic diagnosis of an adrenal neoplasm (ante-mortem or on necropsy). Results: Thirty-three cats met the inclusion criteria for the study. The most common presenting complaints included weakness (n = 12), respiratory signs (n = 4), blindness (n = 4) or gastrointestinal signs (n = 3). Laboratory abnormalities included hypokalemia (n = 18), alkalemia (n = 12), elevated creatine kinase (>3000, n = 5) and azotemia (n = 4). In addition, hypertension was noted in 13 cats. Thirty cats were diagnosed with cortical tumors (17 carcinomas, 13 adenomas) and three cats were diagnosed with pheochromocytomas. Twenty-five cats underwent tests to evaluate the function of the adrenal tumors; 19/25 cats had functional tumors (hyperaldosteronism [n = 16], hypercortisolemia [n = 1], high estradiol [n = 1], and hypersecretion of aldosterone, estradiol and progesterone [n = 1]). Twenty-six cats underwent adrenalectomy, one cat was medically managed and six were euthanized without treatment. Long-term survival postoperatively ranged from 4–540 weeks, with 20 (77%) cats surviving the perioperative period of 2 weeks. The only variable that was found to be negatively associated with survival was female sex. The most common complications noted during the perioperative period were hemorrhage and progressive lethargy and anorexia. Conclusions and relevance: Surgical treatment for feline adrenal tumors (regardless of tumor type) resulted in good long-term survival. Given that pre- and postoperative hypocortisolemia was identified in this study, and, in addition, hypersecretion of more than one adrenal hormone occurred in one cat, adrenal panels prior to surgery may be beneficial as part of the preoperative work-up.